2022
DOI: 10.18178/ijiet.2022.12.9.1708
|View full text |Cite
|
Sign up to set email alerts
|

A Meta Analysis on Augmented Reality Application for Individuals with Intellectual Disability

Abstract: There is a growing interest in utilizing technology tools such as augmented reality to support individuals with disability in general and intellectual disabilities in particular. Therefore, the purpose of this study is to assess the effectiveness of augmented reality technology in improving positive outcomes of individual with intellectual disabilities. Following Arksey and O’Malley and Kitchenham guideline, a meta-analysis of the overall effect of augmented reality on individuals with intellectual disabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Also, Erbas and Demirer [29] came to the conclusion that AR activities play a key role in students' learning by giving them the opportunity to observe and examine organisms and their structures, a task that is normally extremely difficult under traditional teaching conditions. Technology tools such as AR technology provide advantages as a support tool in the process of learning and teaching [46][47][48][49][50]. The positive significant result found in this study may also be attributed to the fact that AR technology is capable of facilitating students' learning and understanding of the material through the activities it provides.…”
Section: Discussionmentioning
confidence: 59%
“…Also, Erbas and Demirer [29] came to the conclusion that AR activities play a key role in students' learning by giving them the opportunity to observe and examine organisms and their structures, a task that is normally extremely difficult under traditional teaching conditions. Technology tools such as AR technology provide advantages as a support tool in the process of learning and teaching [46][47][48][49][50]. The positive significant result found in this study may also be attributed to the fact that AR technology is capable of facilitating students' learning and understanding of the material through the activities it provides.…”
Section: Discussionmentioning
confidence: 59%
“…As the development of VR technology continues alongside other technologies such as augmented reality and mixed reality (Maran et al, 2022;Muhaidat et al, 2022), this preliminary study has demonstrated the potential of VR and acceptability for the use of digital technology in people with intellectual disability to help reduce anxiety and improve attendance at health-care appointments.…”
Section: Discussionmentioning
confidence: 88%
“…In particular, the conceptual foundation for its usage and integration into education is crucial to the success and future integration of digital learning efforts in the educational context [9][10][11]. Although a number of studies indicate critical elements for the adoption of these technologies [9,11], there has been minimal research on incorporating AR into classrooms [12,13], particularly in developing nations such as Saudi Arabia (SA). In its 2030 vision, SA's government places significant emphasis on the development of the higher education system.…”
Section: Introductionmentioning
confidence: 99%